An implementation of activity-based costing (ABC) approach for analysing cost of community-based rehabilitation (CBR) activities for disabled children - Hasan, Haliza; Syed Junid, Syed Mohamed Al Junid; Wan Puteh, Sharifa Ezat; Abd Aziz, Aznidah Firzah; Mohd Nur, Amrizal; Mohd Nordin, Azlin; Jaafar, Nurul Anisah (2017)
Introduction Activity-based costing (ABC) is a method to estimate costs by time motion activity. All activities run in the program were evaluated. Objective The objective of this study is to estimate costs of all activities in Community-based rehabilitation (CBR) program for disabled children. Methodology Time motion study was conducted from March 2015 to April 2016 to determine time taken for each activity run by the assigned staff. A costing form was used to impute cost of CBR activities. The total annual gross income of assigned staff was divided by 22days/month, then 6 hours or 8 hours to calculate cost per minute for each activity. Results The results showed that, total cost for CBR activities in 12 months program was RM 39,408,009 with mean RM 218,933 (range: RM 0 – RM 977,675). The highest cost of routine CBR activity is fardhu ain with mean of RM 72,036 (range: RM 0 – RM62,836) and the lowest mean cost of CBR routine activity is RM 491 (range: RM 0 – RM 1,745). The highest mean cost for support team activities is for medical team with mean of RM 1,336 (range: RM 0 – RM 3,225) and the lowest mean cost is an assessor panel from Department of Education RM 3 (range: RM 0 – RM 280). Conclusion Cost of CBR activities can feasibly be determined using ABC approach. All data obtained can be evaluated for future financial planning by the policy maker to enhance CBR program in future.